2020
DOI: 10.1111/jzo.12781
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal overlaps between leopards (Panthera pardus) and their competitors in the African large predator guild

Abstract: Understanding the mechanisms facilitating coexistence within species assemblages is a key consideration for conservation as intact assemblages are necessary for maintaining full ecosystem function. The African large predator guild represents one of the few remaining functionally intact large predator assemblages on Earth, and as such, represents a unique study system to understand competitive interactions. Yet, relatively little is known of the coexistence mechanisms between some of its intermediately sized me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 72 publications
(126 reference statements)
4
21
0
Order By: Relevance
“…Lion are known to attack and kill leopard [20], steal kills from the smaller-bodied felid [67], and impact cub survival and recruitment rates in leopard populations [68]. However, multiple studies have found leopard to not spatially segregate from lion over larger areas [20,21,22]. In our study landscape, this is likely a result of the species' shared habitat preferences [69]: large-scale avoidance of lion would prevent leopard from accessing many vital resources, particularly in human-impacted areas where resources are more limited, and this may pose a fitness cost to leopard that outweighs the benefits of complete avoidance of the dominant competitor [23].…”
Section: Spatiotemporal Avoidance and Attractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lion are known to attack and kill leopard [20], steal kills from the smaller-bodied felid [67], and impact cub survival and recruitment rates in leopard populations [68]. However, multiple studies have found leopard to not spatially segregate from lion over larger areas [20,21,22]. In our study landscape, this is likely a result of the species' shared habitat preferences [69]: large-scale avoidance of lion would prevent leopard from accessing many vital resources, particularly in human-impacted areas where resources are more limited, and this may pose a fitness cost to leopard that outweighs the benefits of complete avoidance of the dominant competitor [23].…”
Section: Spatiotemporal Avoidance and Attractionmentioning
confidence: 99%
“…Lion are also known to attack and kill leopard (Panthera pardus; 17), which have been shown to move to denser habitats when in close proximity to lion [19] and actively avoid areas where the probability of encountering the dominant competitor is highest [20]. However, multiple studies have found no evidence of lion suppressing leopard at a population level [20,21,22], and it has been theorised that the species may be forced to share space in more anthropogenically impacted areas [23]. Spotted hyaena also typically dominate over leopard [24], and there is evidence of temporal partitioning between the two species [25].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial-temporal overlap between large carnivores and other wild animals in ecosystems is complicated (Rafiq et al 2020). It is an important matter in understanding social diversity regarding competition among predators and predator-prey relationships so that the viable populations of predators and other animals can be sustained (Zhou et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These results from Australia add to the growing body of evidence from other countries that mesopredator suppression or release processes are not ubiquitous. Work from Europe 117,118 , Africa [119][120][121][122][123] , Asia [124][125][126] , North America 9,127 , and South America 128,129 also continue to report an absence of strong top-predator effects on mesopredators, with bottom-up effects appearing to be more strongly associated with mesopredator population changes. Yellowstone National Park in North America appears to be the location where these effects are most apparent, for wolves, with limited evidence for these processes available for almost all other large carnivores ( 2 ; see also 12 ).…”
Section: Discussionmentioning
confidence: 99%